2022
DOI: 10.1001/jamacardio.2022.3485
|View full text |Cite
|
Sign up to set email alerts
|

Professional Preferences and Perceptions of Cardiology Among Internal Medicine Residents

Abstract: ImportanceInternal medicine residents’ professional development preferences were discordant with their perceptions of cardiology in a survey circulated a decade ago; no contemporary data exist. This information is important for effective recruitment and retention of a highly talented and diverse future cardiology workforce.ObjectiveTo identify residents’ professional development preferences and cardiology perceptions, in relation to specialty choice, and compare the findings with those from a decade prior.Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Although the increases in women trainees were significant, providing hope for continued improvement, they lag well behind the percentages of women trainees in all residencies, IM, and general surgery that are now above 40%. IM residents' perceptions of an adverse culture in cardi-ology were similar in 2009 and 2020, 2,3 indicating avenues for improvement. This is supported by underrepresentation of women among IC and EP applicants (12% to 18% and 13% to 15%, respectively, in 2018 through 2021), 7 which suggest applicant choice as a driving factor in subspecialty selection, confirmed by trainee survey.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although the increases in women trainees were significant, providing hope for continued improvement, they lag well behind the percentages of women trainees in all residencies, IM, and general surgery that are now above 40%. IM residents' perceptions of an adverse culture in cardi-ology were similar in 2009 and 2020, 2,3 indicating avenues for improvement. This is supported by underrepresentation of women among IC and EP applicants (12% to 18% and 13% to 15%, respectively, in 2018 through 2021), 7 which suggest applicant choice as a driving factor in subspecialty selection, confirmed by trainee survey.…”
Section: Discussionmentioning
confidence: 96%
“…Both male and female internal medicine (IM) residents are deterred from a cardiology career by perceptions of adverse job conditions, lack of diversity, and negative impacts on family life . In a study of IM subspecialty trainees from 1991 to 2016, CVD programs had the lowest overall percentage and rate of increase of women trainees over time .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also reported that today’s medical students place more emphasis on a specialty with flexible working conditions than a higher salary. [ 4 , 33 , 34 ] Two time-comparison studies of career preferences found that medical students and residents are more likely ( P < 0.05) than their predecessors to emphasize the importance of a career that enables work–life balance, and that has stable working hours [ 9 , 15 ]. Members of Generation-Y are committed to working hard and also expect to take an active role at home and express uncertainty regarding how future plans will influence them holistically [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Millennials (Generation Y), described as persons born between 1980 and 1994 [ 11 , 12 ], are more inclined than previous generations to emphasize the importance of work–life balance [ 13 ] and garnering personal appreciation [ 14 ]. However, few studies have compared changes in the choice of medical specialty selection over time [ 15 ], and none have been performed in Israel. The aim of this study was to compare the importance of certain criteria used by medical students when choosing a medical specialty in 2020 vs. data collected in 2009/10 and subsequently published [ 16 ].…”
Section: Introductionmentioning
confidence: 99%